1976
DOI: 10.1111/j.1469-8986.1976.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular‐Behavioral Interaction—As It Appears Today

Abstract: Research is reviewed concerning the interrelationships among cardiodynamics, blood pressure control mechanisms, somatic activity, and the stimulus parameter of active vs passive coping. Emerging evidence suggests that with passive coping such as classical aversive conditioning, the heart is more under vagal control which is directionally linked with somatic activity, while blood pressure is more dominated by vascular processes. With active coping such as shock avoidance, the heart is under greater sympathetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
229
2
6

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(258 citation statements)
references
References 32 publications
14
229
2
6
Order By: Relevance
“…A primary distinction between active and passive coping stressor tasks is the degree of psychological engagement required for performance completion. The cold pressor task has been classified as a passive coping task because it requires relatively little continuous mental effort to execute (Obrist, 1976). Reaction time and arithmetic tasks require considerable mental effort to execute and are considered active coping in nature.…”
Section: Defensiveness Hostile Individuals Prone To Inhibiting Theirmentioning
confidence: 99%
“…A primary distinction between active and passive coping stressor tasks is the degree of psychological engagement required for performance completion. The cold pressor task has been classified as a passive coping task because it requires relatively little continuous mental effort to execute (Obrist, 1976). Reaction time and arithmetic tasks require considerable mental effort to execute and are considered active coping in nature.…”
Section: Defensiveness Hostile Individuals Prone To Inhibiting Theirmentioning
confidence: 99%
“…A number of studies showed a significant relationship between TABP and CHD (e.g. Matthews and Jennings, 1984;Obrist, 1976;Rosenman et al, 1964;Zyzanski et al, 1979). However it soon appeared that the findings were inconsistent and unstable and that TABP, as it was originally defined, could not be considered a reliable predictor of CHD (Matthews, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in working stress prevention, the training of coping skills is fundamental, and early resiliency literature suggested that cardiovascular responses have an interaction with behavioural change and coping behaviours (Orbrist, 1976). Cardiovascular responses within this context represent adjustments in hemodynamic and its distribution that occurs to meet the metabolic requirements potentially or actually demanded by the task or activity the individual is facing.…”
Section: Psychophysiological Conceptualisations Of Individual Resiliencementioning
confidence: 99%
“…Cardiovascular responses within this context represent adjustments in hemodynamic and its distribution that occurs to meet the metabolic requirements potentially or actually demanded by the task or activity the individual is facing. In addition, Orbrist (1976) suggested that coping behaviours had an association with cardiovascular reactivity. Active coping refers to trying to cope with the situation.…”
Section: Psychophysiological Conceptualisations Of Individual Resiliencementioning
confidence: 99%
See 1 more Smart Citation